Improving Social Studies Learning Outcomes and The Effectiveness of Project-Based Learning - Puryanto, Sidik (research, training and philanthropy institution Natural Aceh, 2023)
The world of education today does not only require students to become experts in the cognitive field but is required to be able to achieve 21st century skills. Based on the analysis and synthesis of journals, the appropriate learning model for facing the 21st century is the Project Based Learning (PjBL) learning model. This study aims to determine the effectiveness of the project based learning (PJbl) learning model in improving student learning outcomes in class IX on conflict material. This research was conducted at SMP 4 Kismantoro Wonogiri, academic year 2022/2023, semester 2. The research method was quasi-experimental (quasi-experimental). The research subjects were 40 students in class IX, which were divided into 17 students in the control class and 23 students in the experimental class. Data analysis used was paired simple t-test, independent t-test and N-Gain scores. The results showed that the project-based learning model could significantly improve the learning outcomes of class IX students at SMP 4 SATAP Kismantoro, with a score of to = -18.164 with sig 0.000 <0.05. Meanwhile, the level of effectiveness of the project-based learning model in social studies subject matter is in the range of 0.3-0.7. The conclusion of this study shows that project-based learning is significantly able to improve learning outcomes in social studies subject matter of conflict in class IX students, and has a moderate level of effectiveness.